Theory and Practice of the Education Science - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2001)
A review of a book by prof. Leonas Jovaiša.
Keywords: Education Science; educational research; educational theories; L.Jovaiša.